OBSERVATIONS ON THE SUMMER FISHERY FOR THE INDIAN MACKEREL RASTRELLIGER KANAGURTA (CUVIER)TN THE GODAVARY ESTUARY - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
There are no reports of occurrence of the mackerel, Rastrelliger kanagurta,in estuaries along the east coast of India, but on the west coast, thesefish are known to ascend the estuaries (Pradhan, 1956; George et ah, 1959 andGeorge, 1965). The present account deals with the observations made on themackerel fishery ol: the Godavary estuary near Yanam, a place situated about20 km from the river mouth, in summers of 1968, 1969 and 1970.